PENGARUH LAYANAN BIMBINGAN KELOMPOK DENGAN TEKNIK ROLE PLAYING TERHADAP SELF AWARNEES SISWA KELAS XI IPA 3 SMAN 9 KOTA BENGKULU - rita fitriyani (Guidance and counseling the university of Prof. Dr. Hazairin. SH, 2019)
The research purpose to find out: 1. self awareness of students who are given services group guidance using role playing techniques. 2. self awareness of students who are given group guidance services without using role playing techniques. 3 differences in self awareness of students who are given group guidance services with role playing techniques and without using role playing techniques. The method used in this research is the experimental method. The population in the study were all students of class XI IPA 3 SMAN 9 bengkulu city. The sample is determined by random technique with the number of 20 students in class XI IPA 3. Technique data analysis that is used is descriptive percentage and t test that processing using program SPSS 20. After the data collected and analyzed obtained the following research results: The level of self awareness of students who are given group guidance services without the use of role playing techniques are generally at a moderate level. The level of self awareness of students in the experimental group who were given group counseling services using role playing techniques were generally at a high level. There is a significant difference between group counseling services with role playing techniques and without using role playing technique to self awareness of students of grade XI IPA 3 SMAN 9 bengkulu city. Then the treatment provided significant effect